Patient Outcomes From a Specialized Inherited Arrhythmia Clinic. (January 2016) - Adler, Arnon; Sadek, Mouhannad M.; Chan, Anita Y.M.; Dell, Edith; Rutberg, Julie; Davis, Darryl; Green, Martin S.; Spears, Danna A.; Gollob, Michael H.
Abstract : Background—: Patients with inherited arrhythmia syndromes are at an increased risk of sudden cardiac death (SCD). Specialized inherited arrhythmia clinics were founded to optimize management and prevention of SCD in this population. However, the clinical effectiveness of these clinics has never been evaluated. Methods and Results—: Clinical outcome data of patients referred to a specialized inherited arrhythmia clinic between 2005 and 2014 for a possible primary electric syndrome or arrhythmogenic right ventricular cardiomyopathy were analyzed. Of 720 patients evaluated, 278 received a definite or probable diagnosis and received long-term management in the inherited arrhythmia clinic. All patients diagnosed with long QT syndrome and catecholaminergic polymorphic ventricular tachycardia received routine β-blocker therapy and demonstrated >90% long-term compliance. In patients with arrhythmogenic right ventricular cardiomyopathy, those demonstrating an arrhythmia burden on Holter or treadmill testing received β-blocker therapy (17%). In diagnosed channelopathy or arrhythmogenic right ventricular cardiomyopathy index cases, 44 patients received secondary prevention implantable cardioverter-defibrillators (long QT syndrome, 9; Brugada syndrome, 8; catecholaminergic polymorphic ventricular tachycardia, 3; short QT syndrome, 1; and arrhythmogenic right ventricular cardiomyopathy, 23). Median follow-up was 4.1 years with 43% having a follow-up period of >5 years. SCD occurred in a single patient (annualized risk of SCD, 0.1% per year). In individuals determined to have clinical or genetic disease by cascade screening, no SCD has occurred over a median follow-up of 5.6 years (55%, >5 years). Low event rates occurred despite a low rate (4.0%) of primary prevention implantable cardioverter-defibrillator utilization. Conclusions—: Longitudinal care in a specialized inherited arrhythmia clinic is associated with a low incidence of SCD and a low rate of primary implantable cardioverter-defibrillator utilization in patients with inherited arrhythmia syndromes. Abstract : Supplemental Digital Content is available in the text.